The Essence of Engineering consultancy contracts (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The engineering consultancy contract is one of the most interesting contracts to study. It arranges the relationships between the consulting engineer, the specialized professional, and the employer. Because The Syrian Civil Law lacks clear texts classifying this contract, it was important to look into this contract's legal nature and discuss its parties’ obligations, in each of the contract’s phases, and know their legal nature and the legal grounds on which they’re based. The essence of an engineering consultancy contract is necessary to be studied under two section, the first deals with the definition of this contract, and the second deals with the obligations of the contract’s parties. مفهوم عقد الاستشارة الهندسيّة يعتبر عقد الاستشارة الهندسيّة من العقود الجديرة بالدراسة، نظراً للدّور الكبير الذي يلعبه في ضمان حسن سير المشاريع الإنشائيّة والصناعيّة الضخمة المنفذة في ظل النهضة العمرانيّة التي يشهدها عالمنا المعاصر، فالعقد ينظّم العلاقة بين المهندس الاستشاري، المهني المختص صاحب الخبرة الفنيّة والمهنيّة، وبين صاحب العمل. ونظراً لافتقاد القانون المدني السّوري لنصوص واضحة تتناول هذا العقد بالتنظيم، فكان لابدّ من البحث في ماهيّة هذا العقد لتحديد طبيعته القانونيّة، والوقوف على التزامات أطرافه، في كل مرحلة من مراحل العقد، لمعرفة تلك الالتزامات وبيان طبيعتها القانونيّة وتحديد الأساس القانوني الذي تقوم عليه. لهذا فإن البحث في مفهوم عقد الاستشارة الهندسيّة يقتضي أولاً التّعريف بعقد الاستشارة الهندسيّة في مبحثٍ أوّل، ثمّ تحديد التزامات أطرافه في مبحثٍ ثانٍ.